Efektivitas tepung tapioka sebagai koagulan alami untuk menurunkan kadar kekeruhan pada pengolahan air bersih - Zainuddin, Marzelina; Kalla, Ruslan; Artiningsih, Andi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
One of the important processes in the clean water treatment process is coagulation. Parameters that influence the coagulation process are pH and coagulant concentration. Tapioca flour can be used as a natural coagulant to reduce turbidity. In this research, river water was used as a source of raw water used in the clean water processing process which has a turbidity of 13.36 NTU. The jar test was carried out to determine the effect of coagulant concentration and pH on reducing turbidity. The coagulation process was carried out using variations in coagulant concentration (1,2,3,4,5 and 6 ppm) and 4 variations in pH (3,5,7 and 9). The results showed that the amount of turbidity reduction varied at each pH used. The coagulation process which takes place in very acidic conditions (pH = 3) results in a greater reduction in water turbidity, namely 3.20 NTU. Almost the same level of turbidity reduction was also seen in the coagulation process which took place at pH 5 and 7, namely 5.22 NTU and 4.30 NTU. Meanwhile, coagulation under alkaline conditions (pH = 9) will result in a smaller decrease in turbidity, namely 11.43 NTU. Based on the final turbidity measurement results, it can be seen that the amount of turbidity reduction is also greatly influenced by the coagulant concentration. Changes in turbidity reduction with variations in coagulant concentration vary at each pH used. At pH 3,5,7 and 9 the decrease in turbidity will be greater at a concentration of 6 ppm. The reduction in turbidity proves the effectiveness of the effect of increasing coagulant concentration and pH using tapioca flour as a natural coagulant in the clean water treatment process.